THE IMPLEMENTATION OF RELIGIOUS AND BOARDING SCHOOL CURRICULUM INTEGRATION AT MADRASAH TSANAWIYAH - Ahmad Baidowi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This research focused on three aspects, such as: model, implementation, supporting and inhibiting factors in implementing the integration Religious and Islamic Boarding School Curriculum at MTs Babussalam Kalibening Mojoagung Jombang. This research used case study approach, the data collection techniques using observation, interviews and documentation. Meanwhile, the data analysis technique in this research used qualitative methods with descriptive analysis techniques (reducing data, presenting data and drawing conclusions). Testing the validity of the data was carried out through extending the research period, triangulation, reference materials, and verification. The results of this research: Changing the boarding school curriculum from religion to Islamic boarding school curriculum and adding the learning time for non-boarding class religious curriculum. The implementation of boarding school classes integration are: the teacher reads the kitab and the students interpret it, students read the kitab in front of the teacher, and the teacher translates it, while the implementation of non-boarding class religious curriculum are: in the form of writing and explanation, meanwhile the Islamic boarding school curriculum consists of the teacher reading the kitab and the students interpreting it, then the teacher translates and explain the kitab.